A supermultiplier demand-led growth accounting analysis applied to the Spanish economy (1998-2019) - Héctor Labat-Moles; Ricardo de Figueiredo Summa (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
In this paper, we analyse the demand-led determinants of Spanish economic growth from 1998-2019. We apply the supermultiplier demand-led growth accounting methodology by Freitas/Dweck (2013) with two modifications: First, we incorporate consumption out of public transfers, following Haluska et al. (2021) and Haluska (2021). Second, we incorporate consumption out of public wages as a source of autonomous demand, theoretically suggested by Serrano/Pimentel (2019). Our demandled growth decomposition highlights (i) public demand and exports as important stable growth drivers, and a decreasing supermultiplier that reduces growth rates; (ii) the indirect effect of a real estate boom in the economic expansion of 1998-2008 caused by increasing public revenues and opening space to the expansion of public demand; (iii) the incapacity of exports to lead the recovery alone, as the latter started only with the resumption of the public and private demand.
Keywords: O47; E11; E12; 330; Supermultiplier; demand-led accounting; Spanish economy